Srī Gurū Grantha Sāhiba jī wicca ditte itihāsaka nāwāṃ te thāwāṃ dā kosha - Mahitāba Siṅgha (SAMP early 20th-century Indian books project ;, 1928)
Research work on the significant religious names and places occuring in Ādi-Granth.